Preparation method of ionic liquid modified metal organic framework material and sulfur dioxide / carbon dioxide adsorption separation application

By modifying the three-dimensional metal organic frame material MIL-101-Cr in ionic liquid, the problem of insufficient adsorption capacity and selectivity in the adsorption separation between SO2 and CO2 is solved, and efficient SO2 adsorption and separation is achieved, which is suitable for industrial flue gas desulfurization and gas separation.

CN120399256APending Publication Date: 2025-08-01INNER MONGOLIA UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510554584.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-29
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing adsorption and separation technology is difficult to achieve efficient selective adsorption of SO2 and CO2, especially in humid environments, the stability and selectivity of the adsorbent are insufficient, and the mass transfer efficiency is low.

Method used

The three-dimensional metal organic frame material MIL-101-Cr is modified with ionic liquid. By introducing ionic liquids at high polar sites, the interaction between SO2 and the functional sites of the material is enhanced, the pore size is regulated to improve mass transfer efficiency, and the adsorption capacity and selectivity are improved.

Benefits of technology

In humid environments, the adsorption capacity and selectivity of SO2 are significantly improved, and the material has strong thermal and chemical stability and good circulation performance. It is suitable for industrial flue gas desulfurization and gas separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120399256A_ABST
    Figure CN120399256A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an ionic liquid modified metal organic framework material and sulfur dioxide / carbon dioxide adsorption separation application, and belongs to the field of metal organic frameworks and gas adsorption separation. A series of high-polarity ionic liquid containing hydrophobic chains is introduced into stable MIL-101-Cr with high BET in a post-modification mode, the chemical action between the adsorbent and SO2 with high polarity is enhanced, the maximum difference of the physical properties of SO2 and CO2 is achieved, and the adsorption capacity and adsorption selectivity of the adsorbent are improved. The thermal and chemical stability of the series ionic liquid modified MIL-101-Cr is good, the series ionic liquid modified MIL-101-Cr shows excellent adsorption selectivity and adsorption capacity under the conditions of high-concentration SO2 (SO2: CO2 = 50: 50) and low-concentration SO2 (SO2: CO2 = 1: 99) at room temperature, and the SO2 adsorption selectivity of the modified MIL-101-Cr is nearly two times higher than that of a parent material MIL-101-Cr. The ionic liquid functionalized metal organic framework material provided by the invention provides a new thought for efficiently capturing SO2 in industrial flue gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the fields of metal-organic frameworks and gas adsorption and separation, and particularly relates to a preparation method of an ionic liquid-modified metal-organic framework material and its application in the adsorption and separation of sulfur dioxide / carbon dioxide. Background Art

[0002] Sulfur dioxide (SO2) is one of the main components of flue gas pollution, which is widely sourced from processes such as fossil fuel combustion, industrial waste gas emissions, and metal smelting. SO2 not only causes environmental problems such as acid rain and haze, but also poses serious hazards to human health, such as triggering respiratory and cardiovascular diseases. In addition, SO2 is both a pollutant and an important chemical raw material in chemical production, and can be used to produce chemicals such as sulfuric acid and sulfur. However, the concentration of SO2 in industrial waste gas is usually low and often coexists with other gases (such as CO2, N2, etc.), making its efficient separation and recovery extremely challenging. Currently, the main SO2 removal technologies include wet desulfurization, dry desulfurization, and adsorption methods, etc. Among them, the wet desulfurization technology is the most widely used, but it has problems such as high energy consumption and difficult by-product treatment. Therefore, there is an urgent need to develop an efficient and energy-saving SO2 adsorption and separation technology to achieve the efficient recovery and utilization of SO2 while reducing environmental pollution.

[0003] Due to advantages such as simple equipment, low energy consumption, and easy operation, the adsorption and separation technology is considered an important means to replace traditional wet and dry desulfurization methods. However, the current SO2 adsorption and separation technology still faces huge challenges, mainly due to the following factors. First, the concentration of SO2 is usually low and coexists with gases such as CO2 and N2, making it difficult to achieve efficient selective adsorption. Second, the molecular diameters of SO2 and CO2 are similar, making it difficult to effectively screen through the pores of the adsorbent (Table 1). In addition, their physical parameters are similar (Table 1), further increasing the difficulty of adsorption and separation. Finally, industrial waste gas often contains water vapor, and water molecules may reduce the stability of the material and compete with SO2, thereby affecting the performance of the adsorbent.

[0004] Table 1 Comparison of Physical Parameters of SO2 and CO2

[0005]

[0006] Traditional porous adsorbents such as activated carbon and zeolites suffer from low surface area, uneven pore size distribution, and a lack of functional sites in SO2 adsorption, resulting in poor adsorption capacity and selectivity. New porous materials such as MOFs, COFs, POCs, POPs, and HOFs are widely used for SO2 capture due to their high surface area, tunable pore structure, and surface chemical properties, and exhibit excellent adsorption performance. Although MOFs have high SO2 adsorption capacity, their large pore size allows gas molecules to easily penetrate and leak, resulting in low SO2 / CO2 separation efficiency. For example, in 2023 and 2024, the research groups of Omar K. Farha (J.Am.Chem.Soc.2023,145,26890-26899) and Yong Cui (J.Am.Chem.Soc.2024,146,31807-31815) reported Zr-TPA-FA (22.7mmol / g, 298K, 1bar) and SJTU-220-(Cr) (35.6mmol / g, 298K, 1bar), respectively. The SO2 adsorption capacity of SJTU-220-(Cr) is the highest value reported in the literature, but its SO2 / CO2 selectivity was not evaluated; while the selectivity of Zr-TPA-FA is relatively low (IAST selectivity is 20.8, SO2 / CO2=1:99, 298K, 1bar). How to improve the selectivity while increasing the SO2 adsorption capacity is an urgent problem to be solved. MOFs usually face problems of water stability and water competitive adsorption, and need to regulate functional sites to achieve efficient adsorption. In contrast, COFs have better stability, but their adsorption performance is usually lower than that of MOFs, probably due to the lack of effective functional sites, such as highly polar metal ions. In addition, some two-dimensional COFs and small-pore tubular materials hinder subsequent molecular mass transfer after capturing gases, resulting in insufficient site exposure, thereby reducing adsorption capacity and separation efficiency. In 2025, Bu Xianhe's research group at Nankai University reported (Nat. Chem. 2025) a flexible hydrogen-bonded organic framework material (HOF-NKU-1). This material achieved a record selectivity at 298K and 1 bar (IAST selectivity > 7000, SO2:CO2 = 10:90) due to its guest adaptive characteristics and shape memory porous properties, providing new ideas for the design of highly adsorption-selective porous materials. However, the SO2 adsorption capacity of HOF-NKU-1 at 298 K is 6.74 mmol / g, which is only 18.9% of that of SJTU-220-(Cr) (35.6 mmol / g). Therefore, the development of adsorbents that can achieve high capacity and high selectivity for SO2 adsorption in humid environments still faces great challenges. Summary of the Invention

[0007] Aiming at the deficiencies of the existing technology, the purpose of the present invention is to provide an ionic liquid-modified three-dimensional stable MOF material and a method for high-capacity and high-selectivity capture of SO2. The present invention proposes to use the three-dimensional metal-organic framework material MIL-101-Cr with an ultra-high BET specific surface area as the substrate, and perform a series of ionic liquid functionalization modifications on it to achieve efficient adsorption and separation of SO2 at room temperature. The introduction of ionic liquids containing high-polarity sites in the material is easy to form a strong chemical interaction with SO2 with a relatively high polarity, making the adsorption effects of SO2 and CO2 more differentiated, and further improving the adsorption and separation performance. The introduction of ionic liquids containing high-polarity sites in the material significantly increases the physical property differences between SO2 and CO2, can enhance the interaction with SO2 with a relatively strong polarity, and realizes the simultaneous improvement of adsorption capacity and adsorption selectivity. The present invention effectively promotes the application of ionic liquid-functionalized MOF materials in the fields of industrial flue gas desulfurization and gas separation, and effectively solves many problems such as limited adsorption capacity, insufficient selectivity, poor water stability, and low mass transfer efficiency of current adsorbents.

[0008] In summary, the present invention selects a stable three-dimensional MOF as the carrier, which has unique advantages such as an ultra-high BET specific surface area, abundant metal ion polar sites, a multi-interpenetrating pore structure, easily functionalizable pore walls, and excellent chemical / water stability. By introducing high-polarity sites such as ionic liquids containing hydrophobic functional domains into the three-dimensional MOFs, the interaction between SO2 and the functional sites of the material is enhanced, and the physical differences between SO2 and CO2 are maximized. In addition, the introduction of hydrophobic functional sites can avoid competitive adsorption of water molecules and improve the mass transfer efficiency by regulating the pore size. The development of a series of ionic liquid-functionalized MOF materials can significantly improve the adsorption capacity and selectivity, and promote their application in the fields of industrial flue gas desulfurization and gas separation.

[0009] To achieve the above-mentioned invention purpose, the present invention provides the following technical solutions:

[0010] The synthesis route and structure of an ionic liquid-modified metal-organic framework material are as follows:

[0011]

[0012] R = Cl, Br, I, HSO4, CH3SO3, CH3COO; n = 1 - 6.

[0013] X represents an ionic liquid coordinated with Cr in MIL-101-Cr.

[0014] The synthesis of MIL-101-Cr in the synthetic route refers to the literature: Nat. Commun. 2017, 8, 485. During the functionalization process of MIL-101-Cr-X ionic liquid (Chem. Rev. 2012, 112, 970 - 1000), MIL-101-Cr, ionic liquid reagent, and solvent were added to a pressure-resistant bottle and stirred at 25 - 150 °C for 12 - 72 h. The ionic liquid reagents include one of 1-ethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazole bromide, 1-ethyl-3-methylimidazolium iodide, 1-butyl-3-methylimidazole bromide, 1-butyl-3-methylimidazole iodide, 1,3-dimethylimidazole iodide, 1, ' 3 3-dimethylimidazole chloride, 1-ethyl-3-methylimidazole acetate, 1-butyl-3-methylimidazole acetate, 1-ethyl-3-methylimidazole hydrogensulfate, 1-butyl-3-methylimidazole hydrogensulfate, 1-ethyl-3-methylimidazole methylsulfonate. The test results show that the ionic liquid-functionalized MIL-101-Cr-X has excellent SO2 adsorption performance, and the SO2 adsorption performance of MIL-101-Cr-EMImCl is as high as 555 cm -1 (STP) / g

[0015] The ionic liquid reagents include, but are not limited to, any ionic liquid reagent that can react with MIL-101-Cr, such as 1-ethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazole bromide, 1-ethyl-3-methylimidazolium iodide, 1-butyl-3-methylimidazole bromide, 1-butyl-3-methylimidazole iodide, 1,3-dimethylimidazole iodide, 1,3-dimethylimidazole chloride, 1-ethyl-3-methylimidazole acetate, 1-butyl-3-methylimidazole acetate, 1-ethyl-3-methylimidazole hydrogensulfate, 1-butyl-3-methylimidazole hydrogensulfate, 1-ethyl-3-methylimidazole methylsulfonate.

[0016] The structural formula is as follows:

[0017]

[0018]

[0019] The solvent for the reaction includes, but is not limited to, any one of organic solvents such as methanol, ethanol, tetrahydrofuran, acetonitrile, 1,4-dioxane, N,N-dimethylformamide, and N,N-dimethylacetamide.

[0020] The mass ratio of MIL-101-Cr: ionic liquid reagent: organic solvent is 1:1 - 100:40 - 1000.

[0021] The temperature of the ionic liquid functionalization reaction is 25 - 150 °C, and the time is 12 - 72 h. The reaction vessel includes, but is not limited to, a glass bottle, a round-bottom flask, or a pressure-resistant bottle. The mixing methods include, but are not limited to, stirring, ultrasonic treatment, or a thermostatic shaker. After the reaction is cooled to room temperature, it is filtered, and the product is washed with any one of low-boiling solvents such as water, methanol, and ethanol, and then placed in an oven to dry to remove the residual solvent to obtain a solid product.

[0022] The present invention also provides a use of the ionic liquid-functionalized metal-organic framework material obtained by the above method of the present invention. This material is used for the adsorption separation of SO2 / CO2 to capture SO2 in flue gas.

[0023] Furthermore, the temperature during adsorption is 25 - 60 °C.

[0024] After the ionic liquid-functionalized metal-organic framework material of the present invention adsorbs SO2, it can be recycled after desorbing SO2. The specific steps for desorbing SO2 are as follows: The functionalized metal-organic framework material after adsorbing SO2 is dried in an oven at 90 - 120 °C for 12 h or subjected to in-situ vacuum desorption in a BET specific surface area analyzer.

[0025] Compared with the prior art, the beneficial effects of the present invention are:

[0026] The present invention discloses a method for the efficient adsorption separation of SO2 / CO2 using an ionic liquid-functionalized metal-organic framework material. Compared with the reported SO2 / CO2 adsorption materials, the ionic liquid-functionalized metal-organic framework material designed by the present invention has the advantages of a simple synthesis method, strong thermal and chemical stability, high SO2 adsorption capacity and good selectivity, and good cycling performance. Description of the Drawings

[0027] Figure 1 is the infrared spectrum of MIL-101-Cr-X

[0028] Figure 2 is the XRD pattern of MIL-101-Cr-X before SO2 / CO2 adsorption

[0029] Figure 3 is the XRD pattern of MIL-101-Cr-X after SO2 / CO2 adsorption

[0030] Figure 4 It is the nitrogen adsorption curve of MIL-101-Cr-X.

[0031] Figures 5-8 It is the SO2 / CO2 adsorption curve of MIL-101-Cr-X.

[0032] Figure 9 It is the SO2 adsorption curves of MIL-101-Cr and MIL-101-Cr-EMImCl at 298K, 313K, and 333K; Figure 10 It is the SO2 adsorption curve of MIL-101-Cr-EMImCl at 273K.

[0033] Figure 11 It is the five-cycle SO2 adsorption curve of MIL-101-Cr-EMImCl at 298K.

[0034] Figures 12-13 It is the SO2 / CO2 adsorption selectivity (1 bar, 298K) of MIL-101-Cr-X and some MOF materials under gas mixtures with different molar ratios of SO2 / CO2 (50 / 50, 1 / 99). Detailed implementation methods

[0035] To make the objectives, technical solutions, and advantages of the present invention clearer, the following further elaborates on the present invention in combination with examples. It should be understood that the specific examples described herein are only used to explain the present invention and are not limited to the present invention.

[0036] Example 1

[0037] The synthesis of MIL-101-Cr refers to the literature: Nat. Commun. 2017, 8, 485. A solution containing chromium(III) nitrate Cr(NO3)3·9H2O (800 mg, 2.0 mmol), HNO3 (2.0 mmol), terephthalic acid (328 mg, 2.0 mmol), and 10 mL of H2O was transferred to the PTFE / Teflon liner of a hydrothermal autoclave, heated at 210 °C for 8 h, and then slowly cooled to room temperature. The solid product was centrifuged to obtain a green powder, which was washed three times with DMF, water, and ethanol at 80 °C for 12 h each. The final product was dried under vacuum at 150 °C for 24 h.

[0038] Example 2

[0039] 1-Ethyl-3-methylimidazolium chloride (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-EMImCl was dried in vacuo at 100 °C for 8 h.

[0040] Example 3

[0041] 1-Butyl-3-methylimidazolium chloride (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-BMImCl was dried in vacuo at 100 °C for 8 h.

[0042] Example 4

[0043] 1-Hexyl-3-methylimidazolium chloride (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-HMImCl was dried in vacuo at 100 °C for 8 h.

[0044] Example 5

[0045] 1-Ethyl-3-methylimidazolium bromide (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-EMImBr was dried in vacuo at 100 °C for 8 h.

[0046] Example 6

[0047] 1-Ethyl-3-methylimidazolium iodide (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-EMImI was dried in vacuo at 100 °C for 8 h.

[0048] Example 7

[0049] 1-Butyl-3-methylimidazolium bromide (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-BMImBr was vacuum-dried at 100 °C for 8 h.

[0050] Example 8

[0051] 1-Butyl-3-methylimidazolium iodide (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-BMImI was vacuum-dried at 100 °C for 8 h.

[0052] Example 9

[0053] 1,3-Dimethylimidazolium iodide (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-MMImI was vacuum-dried at 100 °C for 8 h.

[0054] Example 10

[0055] 1,3-Dimethylimidazolium chloride (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-MMImCl was vacuum-dried at 100 °C for 8 h.

[0056] Example 11

[0057] 1-Ethyl-3-methylimidazolium acetate (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-EMImOAc was vacuum-dried at 100 °C for 8 h.

[0058] Example 12

[0059] 1-Butyl-3-methylimidazolium acetate (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-BMImOAc was dried in vacuo at 100 °C for 8 h.

[0060] Example 13

[0061] 1-Ethyl-3-methylimidazolium methylsulfonate (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-EMImCH3SO3 was dried in vacuo at 100 °C for 8 h.

[0062] Example 14

[0063] 1-Ethyl-3-methylimidazolium hydrogensulfate (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-EMImHSO4 was dried in vacuo at 100 °C for 8 h.

[0064] Example 15

[0065] 1-Butyl-3-methylimidazolium hydrogensulfate (200 mg) and methanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 35 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-BMImHSO4 was dried in vacuo at 100 °C for 8 h.

[0066] Example 16

[0067] 1,3-Dimethylimidazolium iodide (200 mg) and ethanol (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 25 °C for 2 h. The suspension was cooled to room temperature, filtered, and washed with ethanol. The obtained green solid MIL-101-Cr-MMImI was dried in vacuo at 100 °C for 8 h.

[0068] Example 17

[0069] 1,3-Dimethylimidazolium iodide (200 mg) and tetrahydrofuran (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 50 °C for 8 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-MMImI was vacuum dried at 100 °C for 8 h.

[0070] Example 18

[0071] 1,3-Dimethylimidazolium iodide (200 mg) and acetonitrile (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 70 °C for 10 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-MMImI was vacuum dried at 100 °C for 8 h.

[0072] Example 19

[0073] 1,3-Dimethylimidazolium chloride (200 mg) and 1,4-dioxane (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 90 °C for 12 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-MMImCl was vacuum dried at 100 °C for 8 h.

[0074] Example 20

[0075] 1,3-Dimethylimidazolium chloride (200 mg) and N,N-dimethylformamide (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 120 °C for 48 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-MMImCl was vacuum dried at 100 °C for 8 h.

[0076] Example 21

[0077] 1,3-Dimethylimidazolium chloride (200 mg) and N,N-dimethylacetamide (50 mL) were added to a 150 mL pressure-resistant bottle, stirred until completely dissolved, then MIL-101-Cr (100 mg) was added, and the mixture was continuously stirred and reacted at 150 °C for 72 h. The suspension was cooled to room temperature, filtered, and washed with methanol. The obtained green solid MIL-101-Cr-MMImCl was vacuum dried at 100 °C for 8 h.

[0078] Figure 1 It is the infrared spectrum diagram corresponding to Examples 1 - 15. As can be seen from the figure, the ionic liquid-functionalized metal-organic framework material MIL-101-Cr-X was successfully synthesized.

[0079] Figure 2 It is the XRD diagram of MIL-101-Cr-X corresponding to Examples 1 - 15 before SO2 / CO2 adsorption. As can be seen from the figure, MIL-101-Cr-X was successfully prepared.

[0080] Figure 3 It is the XRD diagram of MIL-101-Cr-X corresponding to Examples 1 - 15 after SO2 / CO2 adsorption. As can be seen from the figure, MIL-101-Cr-X still has high crystallinity and a complete structure, showing excellent chemical stability.

[0081] Figure 4 It is the nitrogen adsorption diagram of MIL-101-Cr-X corresponding to Examples 1 - 15 at 77K, indicating that the structure of the ionic liquid-functionalized MIL-101-Cr is stable.

[0082] Figures 5-8 It is the SO2 / CO2 adsorption curve diagram corresponding to Examples 1 - 15. As can be seen from the figure, the ionic liquid-functionalized metal-organic framework material MIL-101-Cr-X prepared in Examples 2 - 15 has better SO2 adsorption performance than the unmodified parent material MIL-101-Cr. Among them, MIL-101-Cr-EMImCl, MIL-101-Cr-EMImBr, and MIL-101-Cr-EMImI prepared in Examples 2, 5, and 6 have outstanding SO2 adsorption performance, and the SO2 adsorption amounts (1 bar, 298K) are 555, 557, and 559 cm 3 g -1 .

[0083] Figure 9 It is the SO2 adsorption curve diagram of MIL-101-Cr and MIL-101-Cr-EMImCl at 298K, 313K, and 333K. In the figure, the SO2 adsorption performance of MIL-101-Cr-EMImCl is better than that of MIL-101-Cr, indicating that this material has strong thermal and chemical stability and a high SO2 adsorption capacity; Figure 10 These are three materials with outstanding SO2 adsorption performance. It is the SO2 adsorption curve diagram of MIL-101-Cr-EMImCl, MIL-101-Cr-EMImCl, and MIL-101-Cr-EMImCl at 273K, and the adsorption capacities are 761, 630, and 647 cm 3 g -1 (1 bar, 273K).

[0084] Figure 11 This is the fifth-cycle SO2 adsorption curve of MIL-101-Cr-EMImCl at 298K, indicating good cycle performance of this material.

[0085] Figures 12-13 This is the SO2 / CO2 adsorption selectivity (1 bar, 298K) of MIL-101-Cr-X and some MOF materials under gas mixtures with different molar ratios of SO2 / CO2 (50 / 50, 1 / 99). Among them, under the condition of an equimolar gas mixture of SO2 / CO2 (1 bar, 298K), MIL-101-Cr-X has better SO2 / CO2 selectivity than the unmodified parent material MIL-101-Cr. It is worth mentioning that the SO2 / CO2 adsorption selectivity of MIL-101-Cr-EMImCl (63.72) is twice that of the unmodified parent material MIL-101-Cr (29.49). The ionic liquid modification strategy significantly improves the SO2 adsorption capacity and the selectivity of SO2 / CO2, which provides an important solution for improving the SO2 adsorption capacity and the selectivity of SO2 / CO2. In addition, the SO2 adsorption capacity and adsorption selectivity of the series of ionic liquid-functionalized MOF materials exceed most of the reported materials ( Figures 12-13 ). These results confirm the superiority of the ionic liquid modification strategy.

[0086] The ionic liquid-functionalized metal-organic framework material MIL-101-Cr-X of the present invention can be reused after desorbing SO2 after adsorbing SO2. Specifically: the functionalized metal-organic framework material after adsorbing SO2 is dried in an oven at 90-120°C for 12h.

[0087] The present invention designs and synthesizes an ionic liquid-functionalized metal-organic framework material MIL-101-Cr-X, which has the advantages of high SO2 adsorption capacity and selectivity, strong thermal and chemical stability of the material, and good cycle performance compared with the reported SO2 adsorption materials. This material has excellent adsorption performance compared with the reported SO2 adsorbents ( Figures 12-13 ). In summary, the ionic liquid-functionalized metal-organic framework material MIL-101-Cr-X designed and synthesized by the present invention has good potential for SO2 / CO2 adsorption separation under industrial application conditions.

[0088] The above description of the embodiments is to facilitate the understanding and application of the present invention by those of ordinary skill in the art. Those skilled in the art can easily make various modifications to these embodiments, including but not limited to modifying all substrate materials capable of synthesizing ion liquid-functionalized porous materials such as POPs, COFs, POCs, HOFs, PAFs, MOCs, etc., modifying the solvents used for ligands, modifying the types and ratios of reaction ligands, solvent ratios, catalyst dosages, etc., modifying the reaction time, temperature, etc., and applying the general principles described herein to other embodiments without creative efforts. Therefore, the present invention is not limited to the embodiments described herein, and the improvements and modifications made by those skilled in the art without departing from the scope of the present invention as disclosed should be within the protection scope of the present invention.

Claims

1. A preparation method of an ionic liquid-modified metal-organic framework material, characterized in that: The method includes, but is not limited to, achieving ion-functionalized MOF materials through pre-assembly or post-modification. The post-modification method for ion-functionalization includes, but is not limited to, modifying MOFs by means of ionic liquids and other means to obtain MOFs containing ion-functional sites. Reacting the metal-organic framework material MIL-101-Cr with an ionic liquid and an organic solvent at a certain temperature to obtain an ionic liquid-functionalized metal-organic framework material MIL-101-Cr-X; Among them, the metal-organic framework material MIL-101-Cr is obtained by the method in Nat. Commun. 2017, 8, 485; The mass ratio of the MIL-101-Cr: ionic liquid reagent: organic solvent is 1: 1-100: 40-1000.

2. The preparation method of an ionic liquid-modified metal-organic framework material according to claim 1, characterized in that, The ionic liquids include, but are not limited to, any ionic liquid reagent capable of modifying MIL-101-Cr such as 1-ethyl-3-methylimidazolium chloride, 1-butyl-3-methylimidazolium chloride, 1-hexyl-3-methylimidazolium chloride, 1-ethyl-3-methylimidazolium bromide, 1-ethyl-3-methylimidazolium iodide, 1-butyl-3-methylimidazolium bromide, 1-butyl-3-methylimidazolium iodide, 1,3-dimethylimidazolium iodide, 1,3-dimethylimidazolium chloride, 1-ethyl-3-methylimidazolium acetate, 1-butyl-3-methylimidazolium acetate, 1-ethyl-3-methylimidazolium hydrogensulfate, 1-butyl-3-methylimidazolium hydrogensulfate, 1-ethyl-3-methylimidazolium methylsulfonate. The structural formula is as follows:

3. The preparation method of an ionic liquid-modified metal-organic framework material according to claim 1, characterized in that, The solvents include, but are not limited to, any organic solvent such as methanol, ethanol, tetrahydrofuran, acetonitrile, 1,4-dioxane, N,N-dimethylformamide, N,N-dimethylacetamide.

4. The preparation method of an ionic liquid-modified metal-organic framework material according to claim 1, characterized in that, The temperature of the ionic liquid functionalization reaction is 25-150 °C, and the time is 12-72 h; the reaction vessel includes, but is not limited to, a glass bottle, a round-bottom flask or a pressure-resistant bottle, and the mixing methods include, but are not limited to, stirring, ultrasonic or constant temperature shaker.

5. The preparation method of an ionic liquid-modified metal-organic framework material according to claim 1, wherein, After the ionic liquid functionalization reaction is cooled to room temperature, it is filtered, and the product is washed with any low-boiling solvent such as water, methanol, or ethanol, and then placed in an oven to dry to remove the residual solvent to obtain a solid product.

6. The preparation method of an ionic liquid-modified metal-organic framework material according to claim 1, characterized in that, The synthesis route and structure of the ionic liquid-functionalized metal-organic framework material MIL-101-Cr-X are as follows: Among them, R = Cl, Br, I, HSO4, CH3SO3, CH3COO; n = 1-6, and X represents the ionic liquid coordinated with Cr in MIL-101-Cr.

7. Use of the ionic liquid-functionalized metal-organic framework material obtained by the method according to any one of claims 1-6, characterized in that, The metal-organic framework material MIL-101-Cr-X is used for SO2 / CO2 adsorption separation to capture SO2 in flue gas.

8. Use of the ionic liquid-functionalized metal-organic framework material according to claim 7, characterized in that, The adsorption temperature is 0 °C to 60 °C.

9. Use of the ionic liquid-functionalized metal-organic framework material according to claim 7 or 8, characterized in that, After adsorbing SO2, the ionic liquid-functionalized metal-organic framework material MIL-101-Cr-X can be recycled after desorbing SO2. The specific steps for desorbing SO2 are as follows: The ionic liquid-functionalized metal-organic framework material MIL-101-Cr-X after adsorbing SO2 is dried in an oven / vacuum drying oven at 25-150 °C for 12-24 h or vacuum in-situ desorption is carried out in a BET specific surface area analyzer.